The Main Tasks of Developing the Professional Competence of Future Technical Specialists on the Basis of Multimedia Tools - Norinov Muxammad Yunus Usibjonovich (Research Parks Publishing LLC, 2023)
In this article, the assessment of professional competence is based on the essence and characteristics of professional formation. The pedagogue's cognitive activity is largely determined by the complexity, dynamics, non-standardity of the things being studied, the influence of boundaries separating social phenomena, their search, uncertainty, which implies observation, the skill of modeling the inner world of the interlocutor. is considered as competence for a certain profession.